RUMAH BELAJAR LANSIA: PUSAT PENGEMBANGAN DAN PENINGKATAN POTENSI LANJUT USIA DI KELURAHAN BUMI WARAS KOTA BANDAR LAMPUNG - Aristoteles Aristoteles; Rinaldo Adi Pratama; Tiyara Saghira; Syangap Diningrat Sitompul; Ahyarudin; Jihan Aferiansyah; Aulia Putri Ariqa; Aflaha Asri; Admi Syarif; Kurnia Muludi; Favorisen R. Lumbanraja (Badan Pelaksana Kuliah Kerja Nyata Universitas Lampung, 2022)
The neglected elderly is one of the impacts of the existing poverty problem, where poverty is not only limited to economic inability, but also the failure to fulfill basic rights and differences in treatment of a person or group of people in living a decent and dignified life. The method of writing this article uses a qualitative-descriptive approach to provide an overview as well as a description of the implementation of the team-based project “Rumah Belajar Lansia”. The implementation project of Rumah Belajar Lansia is focuses on providing benefits for all elderly residents on Jalan Skip Rahayu, Bumi Waras Village, which was welcomed and enthusiastically by involving the role of institutions and the community in its implementation which consists of several programs, namely, re-establishing the Posyandu for the Elderly, implementing ergonomic gymnastics for the elderly, and providing socialization or counseling on physical and psychological health of the elderly. This article is limited to the implementation of the Pejuang Muda Bandar Lampung City program in 2021.